No-tillage mulch with leguminous green manure retention reduces soil evaporation and increases yield and water productivity of maize - Feng Wang; Yulong Wang; Hanqiang Lyu; Zhilong Fan; Falong Hu; Wei He; Wen Yin; Cai Zhao; Qiang Chai; Aizhong Yu (Agricultural Water Management, 2023)
In the Hexi oasis irrigation area, green manure improves the use efficiency of soil, light, heat and precipitation resources during a long fallow period (from the wheat harvest to the later maize sowing). The work aims to determine the optimal utilization patterns of green manure for reducing maize evapotranspiration (ETc) reduction and improvement of grain yield (GY) and crop water productivity (WPc). A two-year field experiment was conducted at a research station in the Shiyang River Basin (Gansu, China) using a completely randomized design with three replications. Five treatments were involved in this study: (i) conventional tillage fallow and leisure without green manures as a control (CT), (ii) tillage with total of green manures incorporated in the soil (TG), (iii) no-tillage with total green manures mulched on soil surface (NTG), (iv) tillage with root incorporated in the soil and aboveground removal of green manures removed (T), (v) no-tillage with aboveground manures removed (NT). The results showed that the soil bulk density was reduced by 1.4–8.9%, and field capacity was increased by 1.0–4.5% under green manure returning. The soil water storage (SWS) at 0–100 cm soil layer was improved during the maize growing season. Compared with CT, maize evapotranspiration (ETc) was significantly reduced by 7.4% due to the significant decline in soil evaporation (E) by 12.8% under the NTG treatment. On average, the maximum root biomass (RBmax) (26.8 g plant–1), aboveground biomass (ABmax) (421.1 g plant–1), GY (15085.5 kg ha−1) and WPc (3.2 kg m−3) of NTG were significantly increased by 79.7%, 25.3%, 34.3% and 39.2%, respectively. Rising RB and falling ineffective ETc contribute to the increase in GY and WPc. For the spring wheat-maize rotation system, NTG is an ideal green manure returning method for achieving high yield and WPc in the arid oasis irrigation area.